Determination of three-dimensional distribution of electrical conductivity in the Earth’s mantle from Swarm satellite data: Time-domain approach - Velímský, Jakub (Earth, planets, and space, 2013)
One of the primary goals of the Swarm multisatellite mission is to determine the 3-D distribution of electrical conductivity in the Earth’s mantle. This paper presents an inversion method based on direct integration of magnetic fields in the time domain, and using the adjoint solution for fast evaluation of data sensitivities to model perturbations. Two tests of the method are presented. The first one is using a 3-D checkerboard conductivity model and noise-free synthetic data. The second test is based on the closed-loop simulation of Swarm mission, including recovery of external and induced fields from simulated data along satellite tracks, and realistic noise estimates.